2014
DOI: 10.1002/pmic.201400013
|View full text |Cite
|
Sign up to set email alerts
|

MBD5 and MBD6 interact with the human PR‐DUB complex through their methyl‐CpG‐binding domain

Abstract: MBD5 and MBD6 are two members of the methyl-CpG-binding domain (MBD) family of proteins that are poorly characterized. Studies performed thus far have failed to show binding of the MBD5 and MBD6 MBD to methylated DNA. Here, we show that both MBD5 and MBD6 interact with the mammalian PR-DUB Polycomb protein complex in a mutually exclusive manner. Strikingly, the MBD of MBD5 and MBD6 is both necessary and sufficient to mediate this interaction. Chromatin immunoprecipitation analyses reveal that MBD6 and FOXK2/PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 48 publications
5
75
0
Order By: Relevance
“…Another example of multiple layers of regulation impinging on a single protein is the tumor suppressor BAP1. This enzyme is activated by ASXL1 to deubiquitylate H2A and can be targeted to certain genomic loci by its association with transcriptional regulators [20,61,92]. BAP1 can furthermore be spatially separated from its targets by ubiquitylation of its C-terminal nuclear localization signal (NLS) by UBE2O, causing mislocalization to the cytoplasm [84].…”
Section: Multiple Layers Of Regulationmentioning
confidence: 99%
“…Another example of multiple layers of regulation impinging on a single protein is the tumor suppressor BAP1. This enzyme is activated by ASXL1 to deubiquitylate H2A and can be targeted to certain genomic loci by its association with transcriptional regulators [20,61,92]. BAP1 can furthermore be spatially separated from its targets by ubiquitylation of its C-terminal nuclear localization signal (NLS) by UBE2O, causing mislocalization to the cytoplasm [84].…”
Section: Multiple Layers Of Regulationmentioning
confidence: 99%
“…10 Previous studies have shown that FOXK2 was involved in many molecular mechanisms, including starvationinduced autophagy, 11 cell adhesion and motility, 12,13 chromatin structure modification, [12][13][14] G/T-mismatch repair 15 and cell cycle regulation. 10 Previous studies have shown that FOXK2 was involved in many molecular mechanisms, including starvationinduced autophagy, 11 cell adhesion and motility, 12,13 chromatin structure modification, [12][13][14] G/T-mismatch repair 15 and cell cycle regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead box K2 (FOXK2) is a forkhead box transcription factor, which was initially recognized as a regulator of IL-2 transcription. 10 Previous studies have shown that FOXK2 was involved in many molecular mechanisms, including starvationinduced autophagy, 11 cell adhesion and motility, 12,13 chromatin structure modification, [12][13][14] G/T-mismatch repair 15 and cell cycle regulation. 16 FOXK2 was also reported to play important roles in the carcinogenesis of breast cancer [17][18][19] and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the MBD‐based approach offers real‐time images of the precise localization of methylated DNA in living cells. Mammalian MBD protein family consist of 11 proteins that are characterized by a methyl‐CpG‐binding domain containing 70–80 amino acids . The dissociation constants of MBD proteins toward methylated DNA were reported to be in the micromolar to nanomolar ranges in different previous studies .…”
Section: Methylated Dna Imaging In Living Cellsmentioning
confidence: 99%